God's Translator: Qu'ran Translation and the Struggle over a Written National Language in 1930s China. (November 2015) - Henning, Stefan
Translation was crucial to the formation of Chinese modernity. While scholarship has centered on the translation of Western texts, I present here a case of translation from a non-Western context: the translation of the Qur'an into Chinese. Translating the Qur'an—fourteen times in the twentieth century—was a strategic intervention into the relations between Muslims and China's non-Muslim majority as well as between Muslims and the Chinese state. I analyze why the first Chinese Qur'an translations in the twentieth century were accomplished by non-Muslims and how the decision to translate among Muslims followed from an internal critique of Muslim collective life in China. In a close reading of an essay from 1931 on Qur'an translation in China by a friend and collaborator of a Chinese Qur'an translator, I seek to identify the strategic risks and the strategic promises inherent in translating the Qur'an in Republican China by situating the translation in between the international and the national, alterity and self-same, and God and the secular.